Influence of heat dumping on the operation of residential micro-CHP systems. (15th December 2015) - Mongibello, Luigi; Bianco, Nicola; Caliano, Martina; Graditi, Giorgio
Highlights: The operations of four different micro-CHP systems are analyzed. A multi-apartment housing situated in Italy is considered as user. The economic optimization of prime movers operations is performed. Heat dumping effects on economic savings, PESs, and pollutants emission are shown. A relatively low heat dumping allows a considerably reduction of the thermal storage size. Abstract: This work deals with the effects of the heat dumping on the operation of four residential micro-CHP (combined heat and power) systems, each composed of a prime mover producing electricity and heat, a thermal energy storage system and an auxiliary boiler. The micro-CHP systems differ from one another on the prime mover, while the same multi-apartment housing situated in Italy has been considered as user. Four natural gas fueled commercial prime movers have been considered, two internal combustion engines and two microturbines, characterized by different electric and thermal powers. For each micro-CHP system, two heat-driven operation strategies, one with heat dumping and one without have been implemented by means of a home-made numerical code developed in Matlab environment, and in both the cases the economic optimization of the operation has been performed using the pattern search algorithm. For each analyzed case, the results are reported in terms of prime mover operating hours, thermal and electrical energy production, natural gas consumption, primary energy and economic savings with respect to separate generation of electricity and heat, and pollutants emission. The results of an economic analysis are also reported. The effects of the variation of the maximum capacity of the thermal energy storage system, and of the auxiliary boiler efficiency on the optimization results are analyzed, and the results relative to the two different operation strategies are compared and discussed. The major result of this study is that, for all the analyzed micro-CHP systems, an optimized application of heat dumping in the micro-CHP system operation permit to considerably reduce the size of the thermal energy storage system with respect to the heat-driven operation strategy without heat dumping.